Research on the Distribution Factors of Urban Sports and Leisure Facilities in Suzhou City Based on Points of Interest - Li, Jingyi (International Journal of Natural Resources and Environmental Studies, 2025)
Physical activity has been well documented to have substantial health benefits. The Report on the Health Status of the Chinese People 2020 noted that, as a result of the epidemic, there had been some changes in the exercise health status of the population, with the average number of steps taken by the Chinese people decreasing significantly, some people being touched by the epidemic to start exercising, and people becoming more concerned about their own health. Sports and leisure space is an indispensable and important part of the urban public service system, and it is the basic carrier and important engine of fitness activities for Chinese residents. Building a higher level of public service system for national fitness is not only an important foundation for promoting the comprehensive development of mass sports, but also an important guarantee for promoting the health of all people. In this paper, based on the POI data of National Geographic Information Resource Directory Service System, the spatial layout of outdoor recreation facilities in Suzhou City is researched by using Nearest neighbor index, Kernel density estimate, Standard deviational ellipse and other methods to summarize the pattern of the urban recreation space and its characteristics, and Multiple Linear Regression is also used to explore the factors influencing the spatial layout of urban recreation facilities. The spatial layout of outdoor recreation facilities in Suzhou City was studied by the methods of Kernel density estimate, Kernel density index, Standard deviational ellipse and so on, to summarize the pattern of urban recreation space, and to explore the influencing factors of the spatial layout of outdoor recreation facilities in Suzhou City by Multiple Linear Regression. The results show that: (1) the spatial distribution of sports and leisure facilities is characterized by "central aggregation and peripheral dispersion". (2) The directionality of the spatial distribution of sports and leisure facilities is not obvious, and the distribution range is more concentrated. (3) Suzhou's resident population, GDP and leisure industry have a significant impact on the density of sports and leisure facilities.